Advanced water remediation from ofloxacin by ionizing radiation. (December 2017) - Esposito, Biagio R.; Capobianco, Massimo L.; Martelli, Alessandro; Navacchia, Maria Luisa; Pretali, Luca; Saracino, Michela; Zanelli, Alberto; Emmi, Salvatore S.
Abstract: The performances of remediation processes initiated by ionizing radiation on ofloxacin are investigated in ambient conditions. The effectiveness of the decomposition of ofloxacin has been assessed both by γ-rays and electron beam in various aqueous solutions differentiated by the dissolved gases (Air or oxygen saturated) and H2 O2 . By HPLC it is shown that ofloxacin is removed according to a first order process vs. dose in any system. O2 accelerates the decomposition rate, while H2 O2 does not seem to enhance any oxidation effect. The simultaneous oxidative-reductive treatment (no additive) demonstrated to have better mineralizing performances than the fully oxidative one (H2 O2 present). Mineralization by γ results to be more efficient than by EB. The Total Organic Carbon decrease was investigated in dependence of dose and of the OH production rate. The latter parameter was changed over 7 orders of magnitude by controlling dose rate and/or by adding H2 O2 . A steep increase of acidity remarks the phases of fluorine-carbon bond break. Highlights: The oxidative-reductive and solely-oxidative decompositions show similar efficiencies. The mid range intermediates of a typical AOP are refractory to mineralization. Both decomposition and mineralization processes fit a first order dependence on dose. Fluorine-carbon bond is retained in earlier ofloxacin fragments. EB mineralization is sluggish due to anoxic conditions.